PENERAPAN CROSSWORD PUZZLE DALAM PEMBELAJARAN COOPERATIVE LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI TATA SURYA KELAS VII SMPN 1 PEKANBARU - Nasution, Mia Marhamah; Syafii, Muhammad; Azhar, Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to determine the increase in student learning motivation by applying the crossword puzzles in cooperative learning in solar system material class VII SMPN 1 Pekanbaru. The benefits of research is by applying crossword puzzles in cooperative learning can increase students' learning motivation in the solar system material. This research was conducted at SMPN 1 Pekanbaru, precisely from February to July 2019. The research design is a pre-experimental design one group pretest-posttest. The instruments used in data collection was a questionnaire motivation ARCS consisting of indicator Attention, Relevance, Confidence, and Satisfaction. Data on student learning motivation was analyzed through descriptive analysis. The results of data analysis for attention indicators increased by 0.37 with the medium category, relevance indicators increased by 0.35 with the medium category, indicators of confidence increased by 0.41 with the medium category, and for satisfaction indicators increased by 0.46 with medium category. The increase in the average student learning motivation is 0.40 with the medium category. Thus it can be concluded that the application of crossword puzzles in cooperative learning can increase learning motivation in solar system material class VII SMPN 1 Pekanbaru.Key Words: Crossword Puzzle, Cooperative Learning, Students’ Motivation.